Pengaruh Model Pembelajaran Bersiklus (Learning Cycle 5E) Terhadap Kemampuan Berpikir Kritis Siswa - Meliana Rambu Kuba; Agus Maramba Meha; Jusuf Blegur (Universitas Muhammadiyah Enrekang, 2020)
The aim of this study was to determine the effect of the 5E Learning Cycle model on critical thinking skills in Grade VII students of SMPN 9 East Kupang in the academic year 2019/2020. This study also aims to determine the level of significance of the two methods in improving critical thinking skills. One of the efforts to overcome this is by implementing the 5 E learning cycle (1 Engagement, Exploration, Exploration, Elaboration, Evaluation) learning model. This research is used quasi-experimental with a posttest-only control group design. The population is class VII, and the sample consist of class VIIA that the experimental class, and class VIIB is the control class. The instrument used was an essay test of critical thinking skills. The normality test used the Kolmogorov Smirnov test, and the homogeneity test used the homogeneity of variances test. Based on the t-test results using the Independent Sample Test with the assistance of SPSS version 25, there is a significant value of 0.000 or less than 0.05. , this shows that there is an influence on students' critical thinking.